Likovna apreciacija v vzgoji in izobraževanju: Primeri kvalitativnih raziskav - Duh, Matjaž; Herzog, Jerneja (University of Maribor Press, 2020)
Art Appreciation In Education: Examples Of Qualitative Research- The scientific monograph consists of 6 main chapters. In the introduction, creativity and appreciation are presented as two fundamental aspects of fine art lessons. In the following, the development of the term ‘art appreciation’ is terminologically defined. The chapter on the basic characteristics of art appreciation describes the factors of art appreciation, The structure of art appreciation is presented next, which includes art knowledge and time as important factors. The next chapter describes the layers of the work of art, since the multi-layered nature of art works permits a variety of approaches to the development of art appreciation. An overview is presented in the next extensive chapter, qualitative empirical research, which systematically describes the design, instruments, implementation, and research results. These were achieved in kindergartens, primary schools, and secondary schools, involving students from various fields of study in Slovenia and abroad.